New physics from ultrahigh energy cosmic rays - Sarkar, S (2003)
Observations of cosmic rays with energies above ~ 4 x 10^{10} GeV have inspired several speculative suggestions concerning their origin. The crucial question is whether or not the spectrum exhibits the expected `GZK cutoff' at this energy -- concerning which there are presently contradictory results. If there is indeed a cutoff, then the sources are cosmologically distant and rather exotic in nature. If there is no cutoff then new physics is required.